Survey on Mutation-based Test Data Generation - Hanh Le Thi My; Binh Nguyen Thanh; Tung Khuat Thanh (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The critical activity of testing is the systematic selection of suitable test cases, which be able to reveal highly the faults. Therefore, mutation coverage is an effective criterion for generating test data. Since the test data generation process is very labor intensive, time-consuming and error-prone when done manually, the automation of this process is highly aspired. The researches about automatic test data generation contributed a set of tools, approaches, development and empirical results. In this paper, we will analyse and conduct a comprehensive survey on generating test data based on mutation. The paper also analyses the trends in this field.